Differences between primary and secondary osteosynthesis for fractures of the lower limb with acute compartment syndrome. Issue 4 (27th April 2017) - Ull, Christopher; Seybold, Dominik; Königshausen, Matthias; Schildhauer, Thomas; Geßmann, Jan
Aims and Objectives: : To analyze the differences between primary and secondary osteosynthesis for fractures of the lower limb with acute compartment syndrome (ACS). Materials and Methods: : From our trauma database, we indentified a total number of 107 patients with 126 fractures of AO/OTA type 41 to 44 and 120 ACS from January 01, 2001 to December 31, 2015 who were treated with primary or secondary osteosynthesis after compartment incision. Results: : 71 patients with 77 fractures of AO/OTA classification type 41 to 44 suffering ACS received primary osteosynthesis after compartment incision (POCI) and were compared to 36 patients with 49 fractures of AO/OTA type 41 to 44 and ACS, who were treated by secondary osteosynthesis after compartment incision (SOCI). Patients with POCI showed a significantly shorter length of stay in the hospital with significantly less necessary surgeries for definitive treatment of the fractures and the soft tissue closure than SOCI patients (p < 0, 001). The overall rate of infections in both groups were 13% without any difference between POCI and SOCI. Conclusion: : The POCI of AO/OTA fractures type 41 to 44 with ACS is a safe and effective procedure for unilateral und single fractures of the lower limb without an increasing infection rate.